Development and application of oxygen nanosensors for the assessment of molecular oxygen in 2D and 3D cell culture - Abohujel, Reem (2023)
Nanoparticle science is a rapidly developing field within a variety of scientific disciplines. Developing nanosensor-based nanoparticles for measuring intracellular oxygen is of great interest as a diagnostic tool. It helps to understand and investigate biological responses that affect health, the status of the disease, and the mechanisms of curative therapies. The measurements are based on changes in luminescence intensity quenched by the increase in oxygen concentration. This approach provides information on cellular spatial and temporal measurement and the assessment of kinetics in multiple biological samples for different applications.